Pengaruh Gratis Ongkir dan Ketepatan Waktu Pengiriman Terhadap Keputusan Pembelian Makanan pada Aplikasi Grab di Kota Bima - Ramadhan, Andra; Haryanti , Intisari; Hamidah, Nur Khusnul (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
The development of online food delivery services has shifted consumer behavior from conventional to digital purchases, including through the GrabFood application in Bima City. However, several constraints exist, such as regional limitations on free shipping programs and delivery delays during peak hours. This study aims to analyze the partial and simultaneous effects of free shipping (X₁) and delivery timeliness (X₂) on food purchasing decisions (Y) on the Grab application in Bima City. This research type is associative with a quantitative approach. Sampling was conducted using a purposive sampling technique with a total of 100 respondents. The data analysis methods utilized include classical assumption tests, multiple linear regression analysis, correlation coefficient analysis, determination coefficient analysis, and hypothesis testing (t-test and F-test) using SPSS v21. The multiple linear regression analysis yielded the equation Y = 38.534 + 0.126X₁ + 0.135X₂. Through the t-test, the free shipping variable has a partially positive and significant effect on purchasing decisions (\(t_{count} = 5.843 > t_{table} = 1.9852\); sig. 0.000 < 0.05). The delivery timeliness variable also has a partially positive and significant effect on purchasing decisions (\(t_{count} = 5.663 > t_{table} = 1.9852\); sig. 0.000 < 0.05). The F-test results demonstrate that free shipping and delivery timeliness simultaneously have a significant effect on purchasing decisions (\(F_{count} = 34.685 > F_{table} = 3.09\); sig. 0.000 < 0.05). The correlation level (R) among the variables falls into the strong category at 0.681, and the coefficient of determination (R Square) shows a contribution of independent variables by 38.7%, while the remaining 61.3% is influenced by other factors outside this research